Advancing research toward faster diagnosis, better treatment, and end of stigma in epilepsy. (18th June 2019) - Pitkänen, Asla; Henshall, David C.; Cross, J. Helen; Guerrini, Renzo; Jozwiak, Sergiusz; Kokaia, Merab; Simonato, Michele; Sisodiya, Sanjay; Mifsud, Janet
Abstract: Seven large European Union (EU)–funded epilepsy‐related research projects joined forces in May 2018 in Brussels, Belgium, in a unique community building event—the epiXchange conference. During this conference, 170 investigators from the projects DESIRE, EpimiRNA, EPISTOP, EpiTarget, EpiXchange, and EpiPGX as well as the European Reference Network EpiCARE, met up with key stakeholders including representatives of the European Commission, patient organizations, commercial partners, and other European and International groups. The epiXchange conference focused on sharing and reviewing the advances made by each project in the previous 5 years; describing the infrastructures generated; and discussing the innovations and commercial applications across five thematic areas: biomarkers, genetics, therapeutics, comorbidities, and biobanks and resources. These projects have, in fact, generated major breakthroughs including the discovery of biofluid‐based molecules for diagnosis, elucidating new genetic causes of epilepsy, creating advanced new models of epilepsy, and the pre‐clinical development of novel compounds. Workshop‐style discussions focused on how to overcome scientific and clinical challenges for accelerating translation of research outcomes and how to increase synergies between the projects and stakeholders at a European level. The resulting advances would lead toward a measurable impact of epilepsy research through better diagnostics, treatments, and quality‐of‐life for persons with epilepsy. In addition, epiXchange provided a unique forum for examining how the different projects could build momentum for future novel groundbreaking epilepsy research in Europe and beyond. This report includes the main recommendations that resulted from these discussions.